(untitled) (Academicia Globe: Inderscience Research, 2024)
In this article , the theoretical and practical directions of increasing the socio-political activity of youth , the harmony of moral qualities of young people, the promotion of the national idea in the process of promotion and campaigning in the process of increasing the social-political activity of youth , the relevance of the issue of the national idea, the nation and their interdependence, and the importance of students-youth the scientific theoretical basis of developing high human qualities such as becoming a professional.